2020
DOI: 10.1038/s41598-020-67221-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity hotspot and unique community structure of foraminifera in the world’s deepest marine blue hole – Sansha Yongle Blue Hole

Abstract: Marine blue holes are precious geological heritages with high scientific research values. Their physical and chemical characteristics are unique because of the steep-walled structure and isolated water column which create isolated ecosystems in geographically restricted areas. The Sansha Yongle Blue Hole (SYBH) is the world's deepest marine blue hole. Here, we generated the first DNA metabarcoding dataset from SYBH sediment focusing on foraminifera, a group of protists that have colonized various marine enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Metabarcoding methods have been used to identify foraminiferal community composition in water (Morard et al, 2018) and sediment samples (Frontalini et al, 2020;Li et al, 2020;Cavaliere et al, 2021). A recent study, however, unraveled extreme variations in the number of SSU rRNA gene copies in the genome of planktonic foraminifera (Milivojević et al, 2021).…”
Section: Beyond Species Identificationmentioning
confidence: 99%
“…Metabarcoding methods have been used to identify foraminiferal community composition in water (Morard et al, 2018) and sediment samples (Frontalini et al, 2020;Li et al, 2020;Cavaliere et al, 2021). A recent study, however, unraveled extreme variations in the number of SSU rRNA gene copies in the genome of planktonic foraminifera (Milivojević et al, 2021).…”
Section: Beyond Species Identificationmentioning
confidence: 99%
“…And to a lesser extent among Tubothalamea (Figure 4). Comparison of our primer set with the primers commonly used in foraminiferal metabarcoding studies (Pawlowski et al, 2014;Li et al, 2020;and Cordier et al, 2019) showed similar outcomes (Figure S1). The lack of Tubothalamea taxa detected using our primers could be due to one or a combination of the following reasons: (1) an absence of this lineage in our samples, (2) challenges in lysing these cells, and/or (3) a lack of ability of our primer to amplify this lineage.…”
Section: New Foraminifera-specific Primersmentioning
confidence: 58%
“…We developed foraminifera‐specific primers to target ~250–300 bp of hypervariable regions of the SSU‐rDNA, aiming for amplicon analyses of community samples, adding to the primers developed by other groups (Cordier et al, 2019; Lejzerowicz et al, 2013; Li et al, 2020; Pawlowski et al, 2002, 2014). Our primer enabled us to characterize and compare foraminiferal diversity across the different habitats including marine, brackish, and freshwater/soil habitats (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations